Benthic Fauna Community in 6 Reservoirs of Loei Watershed, Loei Province - สุริยพงศ์ โยธิน (KKU Science Journal, 2017)
The study aimed to study species, number and diversity of benthos including the relationship between water quality and the number of benthic fauna in 6 reservoirs. Samples were collected every 3 months from January to December in 2009. The results showed that there were 3 Phylums of benthic fauna consisting of phylum mollusca, annelida and arthropoda that could be classified into 32 types, 32 families, 30 genus, and 15 orders. The relationship analysis between water quality and the number of benthic fauna showed that the factors positively related with statistically significant level at 0.05 level. The correlation coefficient of benthic fauna were nitrate (r =0.58), and ortho phosphate (r =0.432). When analyzing the factors affecting benthic fauna, it was found that the amount of nitrate and orthophosphate predation of benthic fauna was statistically significant at 0.05 level.